Programme basis for elaboration of the spatial plan for special purpose area of Tara National Park - Dobričić Milica (Zbornik Radova: Geografski institut "Jovan Cvijić", 2007)
Having in mind the importance of Tara National Park at national (1st category natural heritage of extraordinary importance) and international level (potential reserve of biosphere within the UNESCO MAB programme; heritage on the Serbian preliminary list for the UNESCO World cultural and natural heritage; international center of biodiversity), as well as clauses of the Law on planning and construction according to which a spatial plan for special purpose area has to be adopted for national parks, the Republic Agency for Spatial Planning has prepared a Decision to elaborate a Spatial Plan for Special Purpose Area of Tara National Park, adopted by the Government of the Republic of Serbia in November 2006. This paper deals with the importance and necessity to elaborate the spatial plan for special purpose area; it also gives an overview of the main objectives and goals as well as of the SWOT analysis (state of the art, constraints and potentials).